Government Incentives when Pollution Permits are Durable Goods - Justus Haucap; Roland Kirstein (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2001)
This paper analyzes the incentive effects of pollution taxes versus pollution permits for a revenue maximizing Government that also pursues environmental objectives. In our model, pollution permits are analyzed as durable goods, and the leasing of pollution permits is seen as an equivalent to a pollution tax. We show that environmental policy based on durable pollution permits can be welfare superior to a pollution tax regime. The intuition is that a monopolistic Government would, in order to maximize its revenues, try to restrict the permit sales below the welfare maximizing level. While a pollution tax or leasing charge allows the Government to credibly commit to a monopoly level of pollution in future periods, a system based on durable permits weakens the monopolistic Government?s ability to credibly restrict future sales. Therefore, a pollution tax regime may be better for the environment and simultaneously increase Government revenues, but social welfare is larger with pollution permits. Hence, a regime where the Government cannot commit to monopoly quantities may be preferable from a welfare economic perspective. This argument in favor of durable permits complements more traditional arguments based on information asymmetries and innovation incentives.
Keywords: H2; K3; D7; 330; Emissions Permits; Pollution Tax; Time Inconsistency; Durable Goods; Ökosteuer; Emissionsrechte; Dauerhaftes Konsumgut; Steuerpolitik; Public Choice; Steueraufkommen; Zeitkonsistenz; Wohlfahrtseffekt; Theorie